Ex-ante life cycle impact assessment of insect based feed production in West Africa. (February 2020) - Roffeis, Martin; Fitches, Elaine C.; Wakefield, Maureen E.; Almeida, Joana; Alves Valada, Tatiana R.; Devic, Emilie; Koné, N'Golopé; Kenis, Marc; Nacambo, Saidou; Koko, Gabriel K.D.; Mathijs, Erik; Achten, Wouter M.J.; et al.
Highlights: Study explores the environmental impact of insect based feeds (IBFs) in West Africa. Three IBF production models are ex-ante assessed using life cycle assessments. Impacts of IBFs are mostly determined by environmental loads of rearing substrates. IBF production designs show environmental disadvantages over plant based feeds. IBF systems using low-value substrates show impacts comparable to fishmeal. Abstract: While the idea of using insect based feeds (IBFs) offers great potential, especially in developing countries, the environmental impact of implementation remains poorly researched. This study investigates the environmental performance of IBF production in the geographical context of West Africa. Drawing on published life cycle inventory (LCIs) data, the impact of three different IBF production systems were ex-ante evaluated (ReCiPe method) and compared to conventional feed resources. The explorative life cycle study provides a basis for trade-off analysis between different insect rearing systems ( Musca domestica and Hermetia illucens ) and provides insights on the environmental performance of IBF in comparison with conventional animal- and plant based protein feeds (fishmeal, cottonseed and soybean meal). The impacts of IBFs were shown to be largely determined by rearing techniques and the environmental loads of rearing substrates, attesting advantages to the rearing of housefly ( M. domestica ) larvae on chicken manure and the use of natural oviposition, i.e., substrate inoculation through naturally occurring flies. A comparison with conventional feeds pointed out the environmental disadvantages of current IBF production designs (especially in comparison to plant based feeds) that were largely attributable to their different position in the trophic network (decomposers) and the systems' sub-standard capacity utilisation (insufficient economy of scale effect). When larvae are reared on substrates of low economic value (i.e., waste streams), IBF impacts were comparable to fishmeal. The results of the comparative assessment also highlighted a methodological limitation in the ReCiPe method, which does not account for impacts related to the use of biotic resources. As a consequence, the utilization of naturally grown resources, such as wild anchoveta, was treated as an ecosystem service of no environmental charge, providing disproportionate advantages to the fishmeal system.